Mind the Silver Bullet Thinking: A Multilevel Study on the Impact of Manager Trait Mindfulness on Subordinate Objective Job Performance - Zalis, Ladislav; Prochazka, Jakub; Vaculik, Martin (Frontiers in Psychology, 2019)
This research examines the relationship between trait mindfulness of managers and job performance of their subordinates. We hypothesized that both are positively associated and that this association exist when personality variables are controlled for. We tested our hypotheses in a sample of 40 line managers and their 487 subordinates working in 40 teams within the customer service division of an energy company. We measured managers’ trait mindfulness using the Five Factor Mindfulness Questionnaire and managers’ neuroticism and conscientiousness using the NEO-FFI. We obtained objective data of each subordinate’s job performance captured by the company’s KPIs assessed monthly over a period of six months. We used multilevel regression analyses to test our hypotheses. Results did not support our hypotheses, the regression coefficient from managers’ trait mindfulness to subordinates’ job performance was close to zero and insignificant. In the context of previously reported positive findings, our results suggest that the contribution of trait mindfulness to subordinates’ performance might not exist or could be contingent on contextual factors.